EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN TIME TOKEN BERBASIS POWER POINT TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA DI SMP NEGERI 5 PADANGSIDIMPUAN - Sorta Dameria Harianja; Rahmatika Elindra; Eva Yanti Siregar (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2020)
The aim of this study is to know whether using time token learning model based power point on students’ mathematical creative thinking ability on the topic of two variables linear equations system at the eighth grade students of SMP Negeri 5 Padangsidimpuan. The research was conducted by applying experimental method (one group pretest post test design) with 32 students as the sample and they were taken by using cluster random sampling technique from 259 students. Observation and test were used in collecting the data. Based on descriptive analysis, it was found: (a) the average of using time token learning model based power point was 3.6 (very good category) and (b) students’ mathematical creative thinking ability on the topic of two variables linear equations system before using time token learning model based power point was 52.91 (fair category) and after using time token learning model based power point was 83,17 (very good category). Furthermore, based on inferential statistic by using pair sample ttest, (SPSS version 17), the result showed the significant value was less than 0.05 (0.000<0.05). It means, using time token learning model based power point was effective on students’ mathematical creative thinking ability on the topic of two variables linear equations system at the eighth grade students of SMP Negeri 5 Padangsidimpuan.